2022
DOI: 10.1038/s41598-022-11462-8
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative aberrometry compared to preoperative Barrett True-K formula for intraocular lens power selection in eyes with prior refractive surgery

Abstract: To compare the predictive refractive accuracy of intraoperative aberrometry (ORA) to the preoperative Barrett True-K formula in the calculation of intraocular lens (IOL) power in eyes with prior refractive surgery undergoing cataract surgery at the Loma Linda University Eye Institute, Loma Linda, California, USA. We conducted a retrospective chart review of patients with a history of post-myopic or hyperopic LASIK/PRK who underwent uncomplicated cataract surgery between October 2016 and March 2020. Pre-operati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 28 publications
0
18
0
Order By: Relevance
“…They also reported that the percentage of patients within ±0.5D of target was 56% for intraoperative aberrometry and 47% for Barrett-True K ( P = 0.289) [28 ▪ ]. Other studies with smaller numbers of post-hyperopic ablation patients have shown a similar mean absolute error of approximately 0.5D without significant difference from preoperative calculations [20 ▪▪ ,29,45]. Intraoperative aberrometry may be more accurate in post-hyperopic ablation cases with short axial length in comparison to those with intermediate or long axial length [28 ▪ ].…”
Section: Intraoperative Aberrometry In Eyes With History Of Refractiv...mentioning
confidence: 91%
See 1 more Smart Citation
“…They also reported that the percentage of patients within ±0.5D of target was 56% for intraoperative aberrometry and 47% for Barrett-True K ( P = 0.289) [28 ▪ ]. Other studies with smaller numbers of post-hyperopic ablation patients have shown a similar mean absolute error of approximately 0.5D without significant difference from preoperative calculations [20 ▪▪ ,29,45]. Intraoperative aberrometry may be more accurate in post-hyperopic ablation cases with short axial length in comparison to those with intermediate or long axial length [28 ▪ ].…”
Section: Intraoperative Aberrometry In Eyes With History Of Refractiv...mentioning
confidence: 91%
“…Post-myopic ablation patients are the largest subset of post-refractive patients undergoing cataract surgery, and early approaches to IOL calculation in these patients were unreliable [48]. There has been significant interest in using intraoperative aberrometry in post-myopic ablation patients to improve outcomes, and multiple studies have examined utility in these patients [20 29,42,[45][46][47][48][49][50][51]55]. In fact, the ORA device was initially validated based on a study of its use in post-myopic ablation eyes [48].…”
Section: Post-myopic Keratorefractive Ablationmentioning
confidence: 99%
“…Here, we outline that wavefront-guided devices do not stop with custom ablation. Wavefront devices have come a long way since the original bulky prototypes first used, and now researchers are experimenting with numerous exciting prospects [ 140 , 141 , 142 ]. Now that some of the devices are so small, the possibilities are virtually limitless.…”
Section: Wavefront Sensing Technology To Empower Clinical Ophthalmic ...mentioning
confidence: 99%
“…Therefore, the authors attribute clinically comparable predictive refractive accuracy to both approaches. 56 …”
Section: Iol Power Calculation After Prk and Lasikmentioning
confidence: 99%
“…Therefore, the authors attribute clinically comparable predictive refractive accuracy to both approaches. 56 IOL power calculation after SMILE SMILE as the latest development in the field of laser-ablative CRS has become clinically available in 2011. The technique employs a femtosecond (fs) laser, which in contrast to the excimer laser is capable of dissecting spherocylindrical and aspheric lenticule fragments instead of just planar sections.…”
Section: Iol Power Calculation After Rkmentioning
confidence: 99%